Formulation And Invitro, In Vivo Evaluation Of Mucoadhesive Buccal Tablet Of Enalapril Maleate: Pharmaceutical Science-Buccal tablets of Enalapril Mleate - Joan vijetha R; Balamurugan K (International Journal of Life Science and Pharma Research, 2022)
The buccal area of the mouth mucosal cavity provides an adorable route of administration for systemic and local medication distribution. Among the several transmucosal locations accessible, the mucosa of the buccal cavity was determined to be the most convenient and easily approachable site for the administration of therapeutic drugs as retentive dose forms delivery. The objective of the current research is based on to improve the bioavailability and efficacy of the Enalapril maleate (EM) a commonly used antihypertensive drug through buccal mucosal. The pure drug EM and excipient polymers such as, hydroxypropyl methylcellulose (HPMC K100), Carbopol 934p, Chitosan and polyvinyl pyrrolidone (PVP K30) were obtained from manufacturing industries. EM buccal tablets were prepared using direct compression. The powder blend formulation studies such as Bulk density, tapped density, Hausner ratio, Carr’s index and angle of repose were carried out, moisture absorption study was performed by using 5%W/V agar, residence time was carried out using porcine buccal mucosa, ex vivo permeation was performed using Franz diffusion cell and in vivo drug release for API and formulated tablets were studies using rabbits. The result of our study showed that the powder flow properties were found to be within the limits, moisture absorption study was 67.63%, residence time till 8.15 hrs, ex vivo permeation 99.12% and in vivo drug release was extended till 24 hrs. The bioregion in which it will remain in contact were perfectly done with appropriate evaluation techniques (Residence time), the moisture absorption study was carried out to check how much moisture the tablet can absorbed to release the drug and was found satisfactory. The ex vivo permeation study was performed by Franz diffusion cell to check the drug permeation through buccal mucosa. The in vivo studies were performed on New Zealand rabbits and can be concluded that the drug release from the formulated F6 was better than the marketed API.